2009
DOI: 10.1038/hr.2009.178
|View full text |Cite
|
Sign up to set email alerts
|

ALDH2 genetic polymorphism and the risk of type II diabetes mellitus in CAD patients

Abstract: The prevalence of type II diabetes mellitus (T2DM) in coronary artery disease (CAD) patients has been steadily increasing, especially in East Asian countries. Although many studies have suggested that certain genetic variants may predispose to the development of T2DM, very few studies investigated the genetic link with T2DM in CAD patients of East Asia. In this study, we investigated the relationship between Glu504Lys polymorphism in the acetaldehyde dehydrogenase 2 (ALDH2) gene, a key enzyme of alcohol metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 36 publications
1
37
0
2
Order By: Relevance
“…The characteristics of each case-control are listed in Table 1. There were 5 cases-controls of MI (Takagi et al, 2002;Xue, 2007;Jo et al, 2007;Li, 2008;Bian et al, 2010), 4 of CHD (Xu et al 2007;Guo et al, 2010;Yuguo, 2010;Ping, 2012), 2 of CHD plus diabetes mellitus (Chao, 2009;Xu et al, 2010), and 1 of acute coronary syndrome (Xu et al, 2011). Four studies included unpublished material (Chao, 2009;Yuan, 2009;Yijie, 2010;Ping, 2012).…”
Section: Study Inclusion and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of each case-control are listed in Table 1. There were 5 cases-controls of MI (Takagi et al, 2002;Xue, 2007;Jo et al, 2007;Li, 2008;Bian et al, 2010), 4 of CHD (Xu et al 2007;Guo et al, 2010;Yuguo, 2010;Ping, 2012), 2 of CHD plus diabetes mellitus (Chao, 2009;Xu et al, 2010), and 1 of acute coronary syndrome (Xu et al, 2011). Four studies included unpublished material (Chao, 2009;Yuan, 2009;Yijie, 2010;Ping, 2012).…”
Section: Study Inclusion and Characteristicsmentioning
confidence: 99%
“…After reading the titles and abstracts, 65 studies were excluded because they did not exmaine CAD risk and the ALDH2 gene. The full-texts of the remaining 17 articles were reviewed (Takagi et al, 2002;Xue et al, 2007;Jo et al, 2007;Li, 2008;Wada et al, 2008;Chao, 2009;Yuan, 2009Yuan, , 2010Guo et al, 2010;Hao et al, 2010;Yijie, 2010;Yuguo, 2010;Xu et al, 2007Xu et al, , 2010Xu et al, , 2011Kotani et al, 2012;Ping, 2012). Next, an additional 6 articles were excluded [2 were repeated or overlapping studies (Li, 2008;Yuan, 2009), 2 were not case-control studies (Ji, 2008;Li, 2012); and 2 did not include the full-text (Wada et al, 2008;Kotani et al, 2012)].…”
Section: Study Inclusion and Characteristicsmentioning
confidence: 99%
“…91 This polymorphism also has been linked to increased risk of CAD 109 and complications from diabetes. 110 Ebert et al first used hiPSC-CMs derived from a cohort of sex-matched East Asian individuals carrying this polymorphism and showed that these cells experienced more oxidative stress and apoptosis secondary to toxic aldehyde buildup during ischemic injury. 91 These effects were mediated by reactive oxygen species (ROS)-mediated upregulation of JNK, such that administration of JNK inhibitor (JIP) restored ROS level as well as viability post-ischemia.…”
Section: Disease Modeling Using Patient-specific Hipsc Derivativesmentioning
confidence: 99%
“…The single-nucleotide polymorphism that generates a Glu-to-Lys change at position 487 (E487K) of the cardioprotective enzyme aldehyde dehydrogenase 2 (ALDH2*2) (1, 2) has been linked to both an increased risk of CAD and more severe outcomes (3-6), a higher incidence of hypertension and cancer, and an increase in complications from type 2 diabetes (7-9). The ALDH2*2 genotype is present in ~8% of the human population, predominantly in people of East Asian heritage.…”
Section: Introductionmentioning
confidence: 99%